Managing Private Vehicles in Asian Cities - PHANG, Sock-Yong (Institutional Knowledge at Singapore Management University, 2014)
Asia's rapid urbanization and growing incomes have resulted in a corresponding booming market in motor vehicle sales. In 2013, an estimated 18 million new passenger cars were sold in China. Motor vehicle users generate congestion, pollution, accidents, noise and road damage. Yet, in most cities motor vehicle users often do not pay the full social costs and are therefore implicitly subsidized by non-users. According to the Tom Tom Traffic Index, which is based on GPS data, motorists in the worst congested cities in developed countries spend up to 40% more time for peak hour commutes. This level of delay is relatively benign when compared to the congestion problems in many developing country cities where traffic jams of the ‘monster’ variety have on occasion stretched on for over 100 km and lasted for several days. Congestion and pollution are examples of instances of market failure which justify government intervention. That these problems persist and have grown in magnitude reflect government failure to adequately implement policies to address these issues.